Evaluating Industry-Aligned Skill Development Programs for Persons with Disabilities in Local Public Employment Services - Hasniaty Hasniaty; Uyun Fanny Fahraeni; Sumiati Tahir; Sadly Abdul Djabar (Jurnal Ilmu Manajemen Profitability, 2026)
Inclusive employment remains a critical component of sustainable development, yet persons with disabilities continue to face barriers in accessing formal labor markets due to limited industry-aligned vocational training and weak institutional coordination. This study aimed to evaluate the effectiveness of an industrial needs–based skill development program implemented by the Disability Service Unit of the Makassar City Manpower Office in improving the employability of persons with disabilities. The research employed a qualitative descriptive design. Data were collected through semi-structured interviews, field observations, and document analysis involving 15 informants, including government officials, company human resource managers, special education teachers, disability advocates, and persons with disabilities. The data were analyzed using the interactive model of qualitative analysis consisting of data reduction, data display, and conclusion verification. The findings indicated that the program had not yet achieved full effectiveness in preparing persons with disabilities for competitive participation in the formal labor market. Training activities remained largely administrative and were dominated by traditional skills that were not aligned with contemporary industry requirements. Limited involvement of industry stakeholders, inadequate accessibility, weak monitoring and evaluation mechanisms, and insufficient post-training job placement support further reduced program impact. These results demonstrate that workforce development programs for persons with disabilities require stronger industry collaboration, competency-based training design, and systematic performance evaluation to achieve meaningful employment outcomes. The study contributes to the literature on inclusive workforce development by highlighting the importance of strategic alignment between public employment services and labor market demands in promoting sustainable labor market inclusion.